The Legal Position of Electronic Systems in Digital Forensic Practices under Law Number 1 of 2023 concerning the Criminal Code of Indonesia - Eti Haryati; Dhanang Widijawan; Edy Santoso (Sean Institute, 2026)
This study examines the legal position of electronic systems in digital forensic practices under Law Number 1 of 2023 concerning the Criminal Code of Indonesia. The development of information technology has transformed criminal activities and evidentiary processes, making conventional evidence insufficient to address crimes involving digital data. Therefore, the recognition of electronic information and electronic documents as lawful evidence marks an important step in the modernization of Indonesia’s criminal law. This research uses a normative juridical method with statutory and conceptual approaches, relying on legal materials such as legislation, legal doctrines, journal articles, and scholarly opinions, which are analyzed qualitatively through legal reasoning and interpretation. The findings show that Law Number 1 of 2023 strengthens the position of electronic systems as sources of evidence and supporting infrastructures in the criminal justice system. Digital forensics plays a crucial role in ensuring the authenticity, integrity, and reliability of electronic evidence through identification, collection, analysis, and presentation processes. However, challenges remain, including the absence of standardized forensic procedures, limited institutional capacity, shortage of experts, cybersecurity threats, cross-border jurisdictional issues, and privacy concerns. In conclusion, the effectiveness of electronic evidence depends not only on legal recognition but also on harmonized regulations, adequate infrastructure, professional competence, and strong legal safeguards to ensure justice, legal certainty, and effective law enforcement in the digital era.